Azacitidine with or without Entinostat for the treatment of therapy‐related myeloid neoplasm: further results of the E1905 North American Leukemia Intergroup study. (18th November 2015) - Prebet, Thomas; Sun, Zhuoxin; Ketterling, Rhett P.; Zeidan, Amer; Greenberg, Peter; Herman, James; Juckett, Mark; Smith, Mitchell R.; Malick, Lisa; Paietta, Elisabeth; Czader, Magdalena; Figueroa, Maria; et al.
Abstract: Therapy‐related myeloid neoplasms (tMN) are serious late effects of the treatment of cancer with poor response to conventional treatment. Azacitidine (AZA) has been used to treat patients with tMN but current data are retrospective. We present here 47 tMN patients prospectively enrolled as a specific cohort in the E1905 study.The E1905 study was a randomized phase 2 study (NCT00313586) testing 10 d of AZA (50 mg/m 2 /d) +/− the histone deacetylase inhibitor entinostat (4 mg/m 2 /d PO day‐3 and day‐10). A total of 47 patients [29 therapy‐related myelosyspastic syndrome (t‐MDS) and 18 therapy‐related acute myeloid leukaemia (t‐AML)] were recruited to the study. 24 patients were treated with AZA monotherapy and 23 with AZA+entinostat. The median number of administered cycles was 4, significantly higher in patients treated with AZA (6 cycles vs. 3 cycles, P  = 0·008). Haematological normalization rates were 46% in monotherapy and 17% in the combination arm. Median overall survivals were 13 and 6 months, respectively. The novel 50 * 10 schedule of azacitidine appears effective, with response rates, when given as single agent, comparable to those for patients with de novo MDS/AML treated on the same protocol. However, the combination of AZA and entinostat was associated with increased toxicity and could not be recommended for treatment of tMN.